2022
DOI: 10.3390/jcm11133681
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Efficacy of Intravenous Alteplase before Endovascular Thrombectomy: A Pooled Analysis with Focus on the Elderly

Abstract: Current guidelines advocate intravenous thrombolysis (IVT) prior to endovascular thrombectomy (EVT) for all patients with acute ischemic stroke (AIS) due to large vessel occlusion (LVO). We evaluated outcomes with and without IVT pretreatment. Our institutional protocols allow AIS patients presenting early (<4 h from onset or last seen normal) who have an Alberta Stroke Program Early CT Score (ASPECTS) ≥6 to undergo EVT without IVT pretreatment if the endovascular team is in the hospital (direct EVT). Rates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 31 publications
(54 reference statements)
0
4
0
Order By: Relevance
“…These studies reported no association with the occlusion site, age, or the presence of atrial fibrillation. [32][33][34] A post hoc analysis of the MR-CLEAN-NO-IV trial has demonstrated an association with the first-line thrombectomy technique used. 35 Other parameters may include pre-treatment with antiplatelets or statins.…”
Section: Discussionmentioning
confidence: 99%
“…These studies reported no association with the occlusion site, age, or the presence of atrial fibrillation. [32][33][34] A post hoc analysis of the MR-CLEAN-NO-IV trial has demonstrated an association with the first-line thrombectomy technique used. 35 Other parameters may include pre-treatment with antiplatelets or statins.…”
Section: Discussionmentioning
confidence: 99%
“…As the impact of bridging treatment may differ across subpopulations, better patients’ selection is warranted, distinguishing those who may benefit or conversely be harmed by the IVT+EVT approach. Recent studies reported no association between IVT+EVT treatment effect and the occlusion site, age or the presence of atrial fibrillation [14 ▪ ,15,16]. A posthoc analysis of the MR-CLEAN-NO-IV trial has demonstrated association between treatment effect and the first-line thrombectomy technique used [17].…”
Section: Pre-procedural Managementmentioning
confidence: 99%
“…However, this therapy is only available in comprehensive stroke centers and requires advanced neurovascular expertise in its provision and patient selection. It is also uncertain whether EVT is better used with or without preceding thrombolysis, and the efficacy of both of these therapies is highly time-dependent [ 2 , 3 , 4 , 5 , 6 ]. Therefore, these advancements have created new challenges in the design of efficient provision strategies regarding acute stroke care services.…”
mentioning
confidence: 99%
“…Ultrasound techniques for the pre-hospital identification of LVO in octogenarians should also quickly be evaluated because, in a drip-n-ship setting, these patients might particularly benefit from being transferred directly to an EVT-capable center [ 6 , 27 ]. The strategy of skipping tPA in EVT-eligible LVO patients with a high risk of hemorrhage may also be considered [ 3 ].…”
mentioning
confidence: 99%